Bedside ultrasonography for acute gallstone disease: a diagnostic accuracy study of surgical registrars and emergency medicine physicians. Issue 12 (31st July 2020) - MacDonald, Andrew A.; Richardson, Malcolm; Sue, Lisa; Hakiwai, Angie; Stephenson, George; Harman, Richard; Agraval, Jash
Abstract: Background: Acute gallstone disease, primarily biliary colic and acute cholecystitis, represents a significant burden on surgical services. Prolonged waiting times for ultrasonography to confirm a diagnosis contributes to inefficiency and delays surgery. Bedside ultrasound offers an opportunity for clinicians make a diagnosis more promptly and streamline acute surgery. This study evaluated the reliability of bedside ultrasound performed by clinicians following local training and a trial of its introduction into clinical practice. Methods: This was a prospective inter‐rater reliability study of bedside ultrasound scans performed on patients referred for suspected acute gallstone disease. Results were compared with a formal ultrasound scan in the radiology department. Inter‐rater agreement for the finding of gallstones and the imaging diagnosis of acute cholecystitis was assessed. Results: A total of 124 patients underwent bedside ultrasound scan, 87 (70.2%) performed by surgical registrars. Mean patient age was 48 years (range 19–92 years) with 95 females (76.6%). Inter‐rater reliability for the finding of gallstones showed strong agreement with kappa 0.85 (95% confidence interval 0.76–0.95) whereas for the imaging diagnosis of acute cholecystitis there was a minimal agreement with kappa 0.37 (95% confidence interval 0.18–0.56). Sensitivity and specificity for the finding of gallstones on bedside ultrasound was 93% and 92%, respectively. Conclusion: Bedside ultrasound is accurate for the finding of gallstones, but the imaging diagnosis of acute cholecystitis is more challenging. There remains the potential for this to improve the efficiency of surgical assessment in suspected acute gallstone disease and this supports the ongoing provision of bedside ultrasound in surgical services. Abstract : Bedside ultrasound performed by surgical registrars and emergency medicine physicians is accurate for finding the presence or absence of gallstones, but less so for an imaging diagnosis of acute cholecystitis. This has the potential to improve the efficiency of surgical assessment of patients.